GROUP SELF EDUCATION BY HAELTH REFLETIVE ACTIONS - AN EMPHASIS IN NURSE ASSISTANCE PRACTICE - Ana Maria Dyniewicz (Universidade Federal do Paraná, 1999)
This work presents an account of an experience carried out with small groups of individuals, working as bank employees, in their own place of work, developed under a proposal of assistance practice of educational dimensions, brought into effect by the nurse in the social function of health educator. It is an alternative methodological approach, guided by a conceptual framework built upon my own conceptions, concepts from Leininger's transcultural theory and a didactic and pedagogic approach based on Paulo Freire's problematization theory, and implemented through Charles Maguerez's Arch Method. The whole methodology proposed here worked around the leading question, "Why do people fall ill?". In this methodology it was attempted to recover beliefs, values, experiences and actions which were characteristic of the individuals, as the essence of the educational work directed to these groups. The individuals' expressions, subdivided into culture-analysis, are part of a provisional synthesis upon which a content analysis was carried out. The (non-) conclusions of these reflections/actions/reflections point at a multicausality of the process of becoming ill, which affects the human being in their totality and uniqueness, with particular significance for those who undergo this process. The groups were then led to a construction of dialogical, reflexive, critical conscience about this multicausality and the facilitating action of inter-support, coherent with the individuals' socio-political, economic and cultural context.